WAYS TO IMPLEMENT THE VARIABLE PROGRAM CHILD OF NEW UZBEKISTAN - Salimov Gairat Mukhamedovich (Galaxy International Interdisciplinary Research Journal, 2024)
In physical education of preschool educational organizations, great importance is attached to activities aimed at developing the individuality of the child, his independence in mastering various types of activities. For this purpose, the use of physical exercises, sports games, holidays, training and educational tools that increase motor activity in preschool educational organizations will have a great effect. The program "New Uzbekistan Child" that we recommend consists of three parts, each of which is devoted to a separate stage of preschool childhood: small, medium and large. The main goals of the program are to ensure a healthy lifestyle, development of physical qualities, initial specialization. The introduction of universal human values is to teach the child to understand the leading spheres of existence - people, things, the natural world, as a subject of actions and experiences.